Vangl2 Promotes Hematopoietic Stem Cell Expansion - Bouali, Sarah; Hétu-Arbour, Roxann; Gardet, Célia; Heinonen, Krista M. (Frontiers in Cell and Developmental Biology, 2022)
Regulation of hematopoietic stem cell (HSC) self-renewal and differentiation is essential for their maintenance, and HSC polarity has been shown to play an important role in this regulation. Vangl2, a key component of the Wnt/polarity pathway, is expressed by fetal and adult HSCs, but its role in hematopoiesis and HSC function is unknown. Here we show the deletion of Vangl2 in mouse hematopoietic cells impairs HSC expansion and hematopoietic recovery post-transplant. Old Vangl2-deficient mice showed increased expansion of myeloid-biased multipotent progenitor cells concomitant with splenomegaly. Moreover, Vangl2-deficient cells were not able to effectively reconstitute the recipient bone marrow in serial transplants, or when coming from slightly older donors, demonstrating impaired self-renewal or expansion. Aged Vangl2-deficient HSCs displayed increased levels of cell cycle inhibitor p16INK4a and active β–catenin, which could contribute to their impaired function. Overall, our findings identify Vangl2 as a new regulator of hematopoiesis and HSC recovery post-transplant.